Cryptography a very short introduction - Piper, F. C. (Frederick Charles), 1940-; Murphy, Sean, 1963- (Oxford : Oxford University Press, 2002)
This is an introduction to cryptography & data protection - subjects of considerable social & political importance. In this introduction to how cryptology actually works, the authors highlight its all-pervasive impact on modern society.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Cryptography